2021
DOI: 10.1002/hbm.25654
|View full text |Cite
|
Sign up to set email alerts
|

Development of the visual white matter pathways mediates development of electrophysiological responses in visual cortex

Abstract: The latency of neural responses in the visual cortex changes systematically across the lifespan. Here, we test the hypothesis that development of visual white matter pathways mediates maturational changes in the latency of visual signals. Thirty-eight children participated in a cross-sectional study including diffusion magnetic resonance imaging (MRI) and magnetoencephalography (MEG) sessions. During the MEG acquisition, participants performed a lexical decision and a fixation task on words presented at varyin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 86 publications
(178 reference statements)
1
11
0
Order By: Relevance
“…Our findings showed that these two maturational phenomena are interrelated, with structural changes of the optic radiations mediating the development of alpha oscillations. This result complements previous reports showing a link between the development of the optic radiations and other types of electrophysiological responses, such as early visual evoked responses peaking around 100 ms 66 . Overall, these findings suggest that the maturation of the optic radiations (and possibly a greater fiber spatial orientation coherence) accounts for changes in the precision and frequency 14 of neural synchronization within the alpha band (i.e., rhythmic neural activity every 100 ms).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings showed that these two maturational phenomena are interrelated, with structural changes of the optic radiations mediating the development of alpha oscillations. This result complements previous reports showing a link between the development of the optic radiations and other types of electrophysiological responses, such as early visual evoked responses peaking around 100 ms 66 . Overall, these findings suggest that the maturation of the optic radiations (and possibly a greater fiber spatial orientation coherence) accounts for changes in the precision and frequency 14 of neural synchronization within the alpha band (i.e., rhythmic neural activity every 100 ms).…”
Section: Discussionsupporting
confidence: 91%
“…QSIPrep 33 preprocessed dMRI data were accessed from AWS S3 at s3://fcp-indi/data/Projects/HBN/BIDS_curated/derivatives/qsiprep/ together with individual quality control scores (n=1885, for the preprocessing pipeline description and quality control scores definition see 35 ). The left and the right optic radiations were identified using pyAFQ 34 based on two endpoint regions of interest (ROIs, for a similar pipeline see 66 ): the primary visual cortex and the central part of the thalamus including the lateral geniculate nucleus (defined based on the AICHA atlas, 71 ; minimum distance 3 mm). Three exclusion ROIs were also used to further clean the tract from crossing fibers (temporal pole, and occipital pole from the AICHA atlas, and the posterior portion of the thalamus based on the brainnetome atlas; minimum distance 3 mm 20,72 ).…”
Section: Methods Participantsmentioning
confidence: 99%
“…The pRNFL is located around the optic nerve head (second cranial nerve), which plays a significant role in vision; thus, pRNFL changes may be sensitive to visual changes and vice versa as previously reported ( Lin et al, 2018 ; Wagner et al, 2020 ). The optic tract consists of white matter microstructure ( Rokem et al, 2017 ; Caffarra et al, 2021 ), which has been reported to be associated with the pRNFL thickness ( Ong et al, 2015 ; Mutlu et al, 2017 ). Besides, axons from the eye to the brain leave through the optic nerve head (pRNFL) to the brain via the optic tract ( Raz and Levin, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even the consistent point-by-point differences are generally not very large (Almost all ACI are smaller than 5%) and they do not clearly change with age. We compared the tissue properties in the OR to two non-visual sub-bundles that we used as a point of comparison in a previous study 14 : the corticospinal tract (CST) and the uncinate fasciculus (UNC). We were not able to delineate left CST in 0.1% of subjects and right CST in 0.1% of subjects.…”
Section: Age Bins the First And Last Age Bin Have A Larger Range Of A...mentioning
confidence: 99%
“…Computational tractography uses this directional diffusion information to generate estimates of the trajectories of white matter pathways between different parts of the brain. In the white matter between the LGN and V1, dMRI can be used to accurately delineate the trajectory of the optic radiations (OR) [12][13][14] . Furthermore, owing to the systematic mapping of the visual field in the visual cortex, parts of the OR that transmit information about different parts of the visual field can be systematically parsed based on their endpoints close to the visual cortex 12,15 .…”
Section: Introductionmentioning
confidence: 99%